Effects of Heat Stress on Production Performance, Redox Status, Intestinal Morphology and Barrier-Related Gene Expression, Cecal Microbiome, and Metabolome in Indigenous Broiler Chickens - Liu, Wen-Chao; Pan, Zi-Yi; Zhao, Yue; Guo, Yan; Qiu, Sheng-Jian; Balasubramanian, Balamuralikrishnan; Jha, Rajesh (Frontiers in Physiology, 2022)
This study was done to evaluate the effects of heat stress (HS) on production performance, redox status, small intestinal barrier-related parameters, cecal microbiota, and metabolome of indigenous broilers. A total of forty female indigenous broilers (56-day-old) were randomly and equally divided into normal treatment group (NT group, 21.3 ± 1.2°C, 24 h/day) and HS group (32.5 ± 1.4°C, 8 h/day) with five replicates of each for 4 weeks feeding trial. The results showed that the body weight gain (BWG) of broilers in HS group was lower than those in NT group during 3–4 weeks and 1–4 weeks (p < 0.05). The HS exposure increased the abdominal fat rate (p < 0.05) but decreased the thigh muscle rate (p < 0.01). Besides, broilers in HS group had higher drip loss of breast muscle than NT group (p < 0.01). Broilers exposed to HS had lower total antioxidant capacity (T-AOC) in serum and jejunum, activities of total superoxide dismutase (T-SOD) in the jejunum, glutathione peroxidase (GSH-Px) in the thigh muscle, duodenum, and jejunum; and catalase (CAT) in breast muscle, duodenum, and jejunum (p < 0.05). Whereas the malondialdehyde (MDA) contents in breast muscle, duodenum, and jejunum was elevated by HS exposure (p < 0.05). Moreover, the relative mRNA expression of Occludin and ZO-1 in the duodenum, Occludin, Claudin-1, Claudin-4, ZO-1, Mucin-2 in the jejunum, and the Claudin-4 and Mucin-2 in the ileum was down-regulated by HS exposure (p < 0.05). The 16S rRNA sequencing results showed that the HS group increased the relative abundance of Anaerovorax in the cecum at the genus level (p < 0.05). Cecal metabolomics analysis indicated 19 differential metabolites between the two groups (p < 0.10, VIP >1). The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that the differential metabolites mainly enriched in 10 signaling pathways such as the Citrate cycle (TCA cycle) (p < 0.01). In summary, chronic HS exposure caused a decline of production performance, reduced antioxidant capacity, disrupted intestinal barrier function, and negatively affected cecal microbiota and metabolome in indigenous broilers.